REPRESENTASI HIBRIDITAS GIRL POWER DALAM PENGEMBANGAN KARAKTER SRI ASIH - Salsabilla Nadhira, Alifya; Dwiningtyas Sulistyani, Hapsari; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research is based on the idea that there has not yet been an Indonesian film featuring a female superhero main character with local cultural values. The film